2004
DOI: 10.1080/02652030412331272458
|View full text |Cite
|
Sign up to set email alerts
|

Australian survey of acrylamide in carbohydrate-based foods

Abstract: A method was developed and validated for the determination of acrylamide in carbohydrate-based foods. Solid-phase extraction employing a mixed-bed anion and cation exchange cartridge in series with a C18 extraction disk was used to clean-up water extracts of food samples before analysis by liquid chromatography coupled with tandem mass spectrometry detection. The limit of detection was calculated as approximately 25 microg kg(-1) and the limit of reporting was 50 microg kg(-1). The average method recovery for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Although robust methods have been reported (Roach et al 2003;Croft et al 2004) that can achieve good sensitivity and selectivity of acrylamide for practically all of the relevant food matrixes, the present authors also found that chocolate products are troublesome matrixes, and that selected mass transitions reveal a difficulty in obtaining baseline separation in certain profiles (Roach et al 2003). In addition, multiple responses are observed in each of the mass transitions at a different retention time but close to that of acrylamide, which may cause interference.…”
Section: Introductionmentioning
confidence: 68%
“…Although robust methods have been reported (Roach et al 2003;Croft et al 2004) that can achieve good sensitivity and selectivity of acrylamide for practically all of the relevant food matrixes, the present authors also found that chocolate products are troublesome matrixes, and that selected mass transitions reveal a difficulty in obtaining baseline separation in certain profiles (Roach et al 2003). In addition, multiple responses are observed in each of the mass transitions at a different retention time but close to that of acrylamide, which may cause interference.…”
Section: Introductionmentioning
confidence: 68%
“…In addition to the inherent physical-chemical properties of acrylamide, the nature of food matrix to be tested should also be considered for extraction. Thermally processed potato and cereals are among the foods in which acrylamide formation has been commonly encountered (Biedermann and Grob, 2003;Friedman, 2003;Amrein et al, 2004;Croft et al, 2004;Surdyk et al, 2004;Taeymans et al, 2004;Gö kmen and Palazoglu, 2007;Wenzl and Anklam, 2007). These foods encompass a vast range of different products with many ingredients, processes, recipes and scales of operation.…”
Section: Resultsmentioning
confidence: 98%
“…A lot of studies confirmed the presence of acrylamide in nearly all fried, baked, and roasted foods sold in Germany (Gutsche et al 2002), UK (Ahn et al 2002), Sweden (Svensson et al 2003), Netherland (Konings et al 2003), Hon Kong (Leung et al 2003), Japan (Ono et al 2003), Austria (Murkovic 2004), Australia (Croft et al 2004), Turkey (Şenyuva and Gökmen 2005a), Spain (RufianHenares et al 2007), Finland (Eerola et al 2007), Italy (Tateo et al 2007), Brasil (Arisseto et al 2007), China (Zhang et al 2007), Korea (Koh 2007).…”
Section: Occurrence Of Acrylamide In Foodsmentioning
confidence: 84%